Dialysis Central Venous Catheter Types and Performance. Issue 7 (May 2014) - Gallieni, Maurizio; Brenna, Irene; Brunini, Francesca; Mezzina, Nicoletta; Pasho, Sabina; Giordano, Antonino
The choice of both short-term (nontunneled) and long-term (tunneled) central venous catheters (CVCs) for hemodialysis is a difficult one, due to the large number of available catheters, with very different characteristics and cost. CVC-related complications (in particular infections, thrombosis and inefficient dialysis) can determine ominous consequences and death, with extremely elevated costs due to prolonged hospitalization and expensive procedures. Thus, the correct balance between cost and quality of CVC is required when deciding which kind of CVC should be adopted. In this regard, the design of CVCs has become a very active area of industrial and clinical research, with the ultimate goal of improving the long-term function of the catheter and of reducing complication rates, because even small improvements in the complication or reintervention rates have a positive impact on individual patient care and cost to society. In this article we review the general features of CVCs, including differences between tunneled and nontunneled CVCs, materials and their compatibility with lock solutions, the implications of straight versus precurved design in nontunneled CVCs, lumen and tip features with their clinical implications, catheter coatings and their effect on infection and thrombosis.